Russia's new military doctrine until 2020: Indecisive compromise between traditionalists and reformers - Margarete Klein (Stiftung Wissenschaft und Politik (SWP), 2010)
On 5 February 2010, President Medvedev signed Russia's long-awaited new military doctrine. The doctrine is an attempt to square the circle, namely to ensure continuity to opponents of the army reform that has been underway since the fall of 2008, while at the same time legitimising this reform. This resulted in a compromise document, which does a poor job of concealing these profound differences of opinion. In this respect, the fact that the doctrine lists NATO and the USA as primary dangers should not be overemphasised. After all, the new document certainly opens up avenues for cooperation and makes it clear that the further development of the armed forces will not be oriented primarily towards notions of the enemy from earlier times
Keywords: 320